Exploring Surgeons' Perceptions of the Role of Simulation in Surgical Education: A Needs Assessment (Canadian Medical Education Journal, 2011)
Introduction: The last two decades have seen the adoption of simulation-based surgical education in various disciplines. The current study’s goal was to perform a needs assessment using the results to inform future curricular planning and needs of surgeons and learners.Methods: A survey was distributed to 26 surgeon educators and interviews were conducted with 8 of these surgeons.  Analysis of survey results included reliability and descriptive statistics. Interviews were analyzed for thematic content with a constant comparison technique, developing coding and categorization of themes.Results: The survey response rate was 81%. The inter-item reliability, according to Cronbach’s alpha was 0.81 with strongest agreement for statements related to learning new skills, training new residents and the positive impact on patient safety and learning.   There was less strong agreement for maintenance of skills, improving team functioning and reducing teaching in the operating room. Interview results confirmed those themes from the survey and highlighted inconsistencies for identified perceived barriers and a focus on acquisition of skills only.  Interview responses specified concerns with integrating simulation into existing curricula and the need for more evaluation as a robust educational strategy.Conclusion: The findings were summarized in four themes: 1) use of simulation, 2) integration into curriculum, 3) leadership, and 4) understanding gaps in simulation use. This study exemplifies a mixed-methods approach to planning a surgical simulation program through a general needs assessment.